Challenges and Opportunities for in situ Maintenance of the Native Brazilian Cotton Gossypium mustelinum Miers - Barroso, Paulo Augusto Vianna; Hoffmann, Lúcia Vieira; da Costa, Nataly Duarte Lopes (Frontiers in Ecology and Evolution, 2021)
The native Brazilian cotton Gossypium mustelinum has never been planted. It is tetraploid and may cross with cultivated cotton. Endemic to Northeast Brazil, it was known only in the semi-arid, but expeditions in 2011, 2015 and 2016 localized populations in the coast of Northeast Brazil, Paraiba and Pernambuco, as predicted before by niche simulations, in preservation areas. New climatic modeling shows that it can still be found in Pernambuco Semiarid, despite the lack of herbaria and germplasm banks informations. Historical data shows that the preserved populations are in regions where sympatry did not occur during the last 47 years, Gene flow is unlikely to be a thread, and communication may foster significantly in situ preservation.